Bladder filling in patients undergoing prostate radiotherapy on a MR-linac: The dosimetric impact. (March 2022) - Smith, Gillian Adair; Dunlop, Alex; Barnes, Helen; Herbert, Trina; Lawes, Rebekah; Mohajer, Jonathan; Tree, Alison C.; McNair, Helen A.
Highlights: Patient compliance with bladder filling varies. The majority of dose constraints can be achieved despite variations in bladder filling. For patients on the MR-linac, a small bladder at the start of the session does not indicate mandatory dose constraints will not be met at time of treatment. Abstract: The implementation of adaptive radiotherapy for prostate cancer compensates for inter-fraction motion, at the penalty of increased time in room. The subsequent increase in bladder filling may impact dosimetry, which we have investigated on ten patients treated on the MR-linac. Patients drank water before treatment, to achieve a bladder volume of 200–300 cm 3 . Bladder and bowel were re-outlined offline on 140 images and plans recalculated. All mandatory bladder dose constraints and 99.1% of bowel constraints were achieved at time of treatment, despite varying bladder volumes and varying adherence to original bladder filling guidance.